2021
DOI: 10.3390/su13158489
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Potential Influence of WeChat Engagement on Bonding Capital, Bridging Capital, and Electronic Word-of-Mouth Intention

Abstract: As the most prevalent social media platform in mainland China, WeChat enables interpersonal communication among users and serves as an innovative marketing platform for enterprises to interact with consumers. Although numerous studies have investigated the antecedents of electronic word-of-mouth (e-WOM), WeChat users’ specific behaviors still receive limited academic attention. Drawing from social capital theory and social exchange theory, this article develops a model to systematically explore three different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
(174 reference statements)
0
4
0
Order By: Relevance
“…Users become invested in the online community and participate more actively when they believe that their views and goals are encouraged and consistent with those of other users [10,27,31]. Sharing and liking have a positive effect on social capital, while social capital has a positive effect on e-WOM intention [33]. Finally, greenwashing perception has a significant impact on customer brand engagement indirectly through green word of mouth [34].…”
Section: Maintaining User Participation Within An Online Communitymentioning
confidence: 99%
“…Users become invested in the online community and participate more actively when they believe that their views and goals are encouraged and consistent with those of other users [10,27,31]. Sharing and liking have a positive effect on social capital, while social capital has a positive effect on e-WOM intention [33]. Finally, greenwashing perception has a significant impact on customer brand engagement indirectly through green word of mouth [34].…”
Section: Maintaining User Participation Within An Online Communitymentioning
confidence: 99%
“…Through communication with users, it allows them to participate in the research and development, design, production, and other aspects of enterprise products. This not only allows users to have emotions about the company's products and increase their willingness to purchase, but also allows users to share products through WOM, achieving the goal of reducing advertising costs and increasing product exposure [12]. In the absence of information technology, people relied on the form of word of mouth to transmit information, which is consistent with the literal meaning of WOM and is itself a form of information dissemination.…”
Section: Social Media and Word-of-mouth Marketingmentioning
confidence: 99%
“…Additionally, previous investigations have theorized and empirically demonstrated the different dimensions of perceived overload [16,20]. One study of the ICT-productivity paradox identified three essential components of technology overload; namely, information dimension, communication dimension, and system feature dimension [33]. Information overload arises when the quantity and complexity of the data that must be stored and processed overwhelms an individual's information processing capacity [12].…”
Section: The Association Between Perceived Overload and Social Media ...mentioning
confidence: 99%